2020
DOI: 10.1108/qrfm-04-2020-0053
|View full text |Cite
|
Sign up to set email alerts
|

Investment behaviour of women entrepreneurs

Abstract: Purpose The purpose of this paper is to understand the new kind of investors – women entrepreneurs – and to find out the factors that drive their investment behaviour and investment decisions. Design/methodology/approach The approach of qualitative enquiry was used for the research in which 18 in-depth exploratory interviews were conducted to identify the determinants of the investment behaviour shown by women entrepreneurs, a growing segment in investment. The accumulated data was analysed using open coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Ref. [23] identifies some critical features that women entrepreneurs felt they looked for to operate their organizations. They made a comparative analysis of South African and Polish female entrepreneurs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ref. [23] identifies some critical features that women entrepreneurs felt they looked for to operate their organizations. They made a comparative analysis of South African and Polish female entrepreneurs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Kappal and Rastogi (2020) emphasized in their studies and confirmed that well-informed, educated, and more financially skilled people can cope up with their finances, which as a result helps to make better decisions for investment. Therefore, it becomes necessary for women entrepreneurs to be financially literate and well-equip themselves.…”
Section: Literature Reviewmentioning
confidence: 67%
“…Hibbert et al (2004) pointed out that financial prudence demonstrated by family and parents significantly influences the financial wit of a young adult. Kappal and Rastogi (2020) also highlighted that financial socialization developed by parents increased investment habits in their adulthood. Besides this guidance of family, social factors such as friends, relatives, and print or digital media drive the financial decision (Akhtar et al 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Three factors affect a person's consumptive behaviour: cultural, social, and personal factors (Wahyuni et al, 2019). There is empirical evidence that women make less investment than men because men are more confident than women, resulting in less financially prepared as they approach retirement (Kappal & Rastogi, 2020). There are even findings if women are more courageous in taking business risks than investment risks (Agarwal & Lenka, 2018).…”
Section: Introductionmentioning
confidence: 99%